2004
DOI: 10.1364/opex.12.001097
|View full text |Cite
|
Sign up to set email alerts
|

Equifrequency surfaces in a two-dimensional GaN-based photonic crystal

Abstract: We established the angular conditions that maintain the quasi-phase matching conditions for enhanced second-harmonic generation. To do that, we investigated the equifrequency surfaces of the resonant Bloch modes of a two-dimensional periodic, hole-array photonic crystal etched into a GaN/sapphire epitaxial structure. The equifrequency surfaces exhibit remarkable shapes, in contrast to the simpler surfaces of a one-dimensional structure. The observed anisotropy agrees well with the surfaces calculated by a scat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…This non-perpendicular light transportation causes a shift in the wavelength of the reflected light, which corresponds to the band distribution at a certain transportation angle. [17,18] According to this, the data from this one fixed angle measurement is not sufficient to generate the whole band structure to match our theoretical calculation; however, the reflection peaks from the spectrum are able to clearly show the existence of the photonic bandgap. Experimentally, there are a few issues associated with the relatively noisy spectra that could contribute to the mismatch.…”
mentioning
confidence: 84%
“…This non-perpendicular light transportation causes a shift in the wavelength of the reflected light, which corresponds to the band distribution at a certain transportation angle. [17,18] According to this, the data from this one fixed angle measurement is not sufficient to generate the whole band structure to match our theoretical calculation; however, the reflection peaks from the spectrum are able to clearly show the existence of the photonic bandgap. Experimentally, there are a few issues associated with the relatively noisy spectra that could contribute to the mismatch.…”
mentioning
confidence: 84%
“…The EFS are obtained by the intersection of the dispersion surfaces and the horizontal plane associated with a constant value ofω . [27][28][29][30][31][32][33][34] Cowan and Young 18 have studied theoretically the SHG produced by coupling of both the fundamental and the SH fields into resonant Bloch modes. They concluded that by optimising the photonic structure, enhancement by up to six orders of magnitude may be obtained.…”
Section: Methodsmentioning
confidence: 99%
“…By using the calculated EFS, 22,34 it is possible to identify the geometrical configurations that will allow confinement to be obtained or QPM to be satisfied in the available wavelength range of the laser.…”
Section: Experimental Second-harmonic Generationmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] These optical structures contain typical feature sizes significantly smaller than the wavelength of light, and thus qualify as true "nanophotonic" devices when the submicron emission wavelength typical of GaN-based materials is taken into account. Potentially, based on such photonic crystal nanocavities, light emitting diodes ͑LED's͒ and lasers could be designed with enhanced light extraction efficiency and reduced lasing threshold, thus enabling optoelectronic integration on an unprecedented scale.…”
Section: Introductionmentioning
confidence: 99%